Chlorhexidine Vs. Sterile Vaginal Wash During Labor to Prevent Neonatal Infection - Nancy L. Eriksen; Keri M. Sweeten; Jorge D. Blanco (Hindawi Limited, 1997)
Objective: The purpose of this study was to determine if a dilute solution of chlorhexidine used as a one-time vaginal wash intrapartum can reduce the use of postnatal antibiotics and neonatal infection.